Waste reduction in barwon dining chair production process using the failure mode and effect analysis (fmea) method on CV. Valasindo Sentra Usaha (Research and Social Study Institute, 2021)
The furniture industry has a vital role in economic growth in Indonesia by one of the activities that are international trade. During the last year, the export value of the furniture industry has increased. It can make an increase of industrial competition in the global market. Therefore, production efficiency needs to be improved under the four pillars that affect global market competitiveness. This study focuses on the Barwon Dining Chair sub-product because it has the most and constant demand with an average demand is 57 units per month while the company experiences delay until 88% with an average delay of 14 days. Determination of Value Added (VA), Non-Value Added (NVA), and Necessary Non-Value Added are used to describe the current Value Stream Mapping (VSM) as an explanation of the production process flow. Failure and Effect Analysis (FMEA) is used to identify a system with the risk of failure and its consequences by giving values from severity, occurrence, and detectability and generating the largest number of RPN assembly stations at 45. The improvements are warehouse rack design and the box at the assembly station, reducing the time to approximately 2 minutes.